Pengaruh Moralitas, Religiusitas, Dan Sosialisasi, Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Agustina Christina Patty; Dirk Berly Tehuayo (P3M Politeknik Negeri Ambon, 2024)
This research aims to determine the influence of morality, religiosity and socialization on individual taxpayer compliance. Religiosity is relevant to the Theory of Planned Behavior, while morality and socialization are relevant to attribution theory. This research is a quantitative research with 50 individual taxpayers registered as respondents at the Pratama Ambon KPP (Tax Service Office). The sample collection technique used was the non-probability sampling method. The data used is primary data using a questionnaire distributed via Google Form, and visited directly by taxpayers, who in this case are research respondents. The results of distributing questionnaires were collected first, after which they were processed using IMB SPSS version 25. The results of this research show that morality, religiosity and socialization have a positive and significant effect on individual taxpayer compliance. Keywords: Morality, Religiosity, Socialization, Individual Taxpayer Compliance.